A INFLUÊNCIA DA INFLAÇÃO DIAGNÓSTICA NO DISCURSO DA ESCOLA SOBRE O COMPORTAMENTO INFANTIL - Monteverde, Eudes Alexandre (2021)
In Western European culture, until around the 15th century, the child was considered a miniature adult and the concept of childhood was practically non-existent. However, from that moment on, a number of moralists and educators began to have a different opinion on the subject, therefore, the first concepts of childhood emerged, with their particularities and later the idea of separating children from adults, because this mixture , according to them, made them spoiled and ill-mannered. Thus, in the following centuries, the control of children's behavior becomes part of the concern, mainly, of educators, which is the focus of our study. The proposed objective is to analyze the school's discourse on child behavior and learning considered outside school standards, among children in Early Childhood Education, and whether they have been influenced by the pharmaceutical industry in the increase in the number of diagnoses of mental disorders among children. in preschool age. The research is based on the theoretical assumptions of childhood and human behavior scholars. The methodological approach used was that of exploratory research, through a case study, with teachers, supervisor and school director of a Municipal Center for Early Childhood Education (CMEI), in the municipality of Boa Esperança - Espirito Santo. Data collection took place through a semi-structured interview. Data analysis was performed based on the theorists studied and the discourse analysis methodology. In our research, the influence of the medicalizing discourse was evidenced, which has become increasingly strong, with the diagnostic inflation that has been happening with each new edition of the DSM (Diagnostic and Statistical Manual of Mental Disorders or Diagnostic and Statistical Manual of Mental Disorders). Mental Disorders), especially in relation to childhood. The search for an ideal behavior, with homogeneous classes and children who learn at the same pace, has led educators to understand that medicine has an explanation and medicalization is a solution to this anguish we suffer.